Dampak Dukungan Platform Digital dalam Memotivasi Guru Tersertifikasi - Verawaty Abdullah; Rahmisyari; Arifin (Teewan Journal Solutions, 2025)
This study was conducted with the aim of determining the impact of digital platform support in motivating certified teachers in elementary education in Elementary Schools in South Bolaang Mongondow Regency. The type of research used in this study is a qualitative type with a case study method approach. The informants in this study were informants who truly understood and were related to the object of the study.The results of this study indicate that digital platform support can provide motivation to certified teachers in improving their personality competencies in the era of independent learning. Digital platforms not only help teachers improve their professional competencies, but also improve personality competencies which are very important in the era of Independent Learning. By improving personality competencies, teachers can be more effective in managing classes, guiding students positively, and being good examples, which ultimately contribute to achieving more holistic and student-centered educational goals.The strategy for improving the personality competencies of certified teachers in South Bolaang Mongondow Regency in elementary education in the era of Independent Learning relies heavily on collaboration and the use of technology to support teacher self-development. Through continuing education, independent training, learning communities, and developing social skills, teachers can improve their personality competencies which are very important to support quality and student-centered learning. This will have a positive impact on student learning in elementary schools in the region.